2021
DOI: 10.3390/w13192717
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Machine Learning Models for Structural Dam Behaviour Interpretation and Prediction

Abstract: The main aim of structural safety control is the multiple assessments of the expected dam behaviour based on models and the measurements and parameters that characterise the dam’s response and condition. In recent years, there is an increase in the use of data-based models for the analysis and interpretation of the structural behaviour of dams. Multiple Linear Regression is the conventional, widely used approach in dam engineering, although interesting results have been published based on machine learning algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…However, validating these models based on the dam engineer's knowledge is fundamental for their adequate use. This issue is tackled in the paper by Mata et al [45] "Validation of Machine Learning Models for Structural Dam Behaviour Interpretation and Prediction". The authors present a methodology based on several validation techniques, including historical data validation, sensitivity analysis, and predictive validation for the practical application of data-based models for structural dam behavior prediction in daily dam surveillance activities.…”
Section: Contributions To Current Special Issuementioning
confidence: 99%
“…However, validating these models based on the dam engineer's knowledge is fundamental for their adequate use. This issue is tackled in the paper by Mata et al [45] "Validation of Machine Learning Models for Structural Dam Behaviour Interpretation and Prediction". The authors present a methodology based on several validation techniques, including historical data validation, sensitivity analysis, and predictive validation for the practical application of data-based models for structural dam behavior prediction in daily dam surveillance activities.…”
Section: Contributions To Current Special Issuementioning
confidence: 99%
“…However, conventional models are difficult to adapt to the complex nonlinear relationship between multi-factors and effect sizes, and the accuracy of model predictions is hard to guarantee. With the development of machine learning (ML) technology, ML-based models are widely used to explain the structural behavior of dams [ 6 ]. Moreover, the existing prediction models only consider the main influencing factors, such as water pressure, temperature and aging, but do not consider the chaotic components that may be included in the deformed time series, which further limits the improvement of fitting accuracy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Hooshyaripor et al [15] reported higher accuracy on a synthetic dataset generated by means of copulas based on the independent relationship between height and volume of water in the reservoirs. ML algorithms have also been applied to other dam safety problems, such as the prediction of dam behaviour [16,17], the detection of anomalies [18][19][20] based on monitoring data, or the prediction of flood maps [21,22].…”
Section: Introductionmentioning
confidence: 99%